Pengaruh Kinerja Keuangan Terhadap Pengungkapan Sustainability Report Perusahaan Pertambangan - Antonius Bimo Rentor; Ester Christianty (CV. Ulil Albab Corp, 2025)
Environmental and social problems make companies start to pay attention to long-term development. Nowadays, companies do not only focus on profit, but companies must also play a role and participate in the welfare of the local community (people) and actively contribute to preserving the environment (planet). Therefore, the government requires public companies to publish sustainability reports as a solution to overcome environmental problems. This research aims to test and analyze related influences on financial performance of sustainability report disclosures. This type of research is quantitative with a descriptive approach. The data used are annual reports and sustainability reports obtained from the official website of the Indonesia Stock Exchange and the official websites of each mining company for 2019-2023. The sampling technique used purposive sampling so that 60 samples were obtained from 12 mining companies. The research results show that return on assets and debt to equity ratio influence sustainability report disclosure.